(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Total Quality Management (TQM), originally developed for the manufacturing industry, has gained considerable traction in educational institutions aiming to improve academic quality and administrative effectiveness. This study explores the relevance, implementation, and impact of TQM principles in the higher education sector. By reviewing foundational literature and analyzing case studies, the research identifies how TQM fosters a culture of continuous improvement, stakeholder involvement, and systemic reform. It further examines the potential of TQM in enhancing educational outcomes in transitional contexts like Uzbekistan, where quality assurance systems are still evolving.